Analysis of liposome model systems by time‐of‐flight secondary ion mass spectrometry. (27th October 2014) - Lovrić, Jelena; Keighron, Jacqueline D.; Angerer, Tina B.; Li, Xianchan; Malmberg, Per; Fletcher, John S.; Ewing, Andrew G.; Lee, Yeonhee; Moon, DaeWon; Kang, Hee Jae; Kim, Kyung Joong; Lee, Tae Geol; et al.
<x xml:space="preserve">Abstract</x> Time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS) is an important technique for studying chemical composition of micrometer scale objects because of its high spatial resolution imaging capabilities and chemical specificity. In this work, we focus on the application of ToF‐SIMS to gain insight into the chemistry of micrometer size liposomes as a potential model for neurotransmitter vesicles. Two models of giant liposomes were analyzed: histamine and aqueous two‐phase system‐containing liposomes. Characterization of the internal structure of single fixed liposomes was carried out both with the Bi3+ and C60+ ion sources. The depth profiling capability of ToF‐SIMS was used to investigate the liposome interior. Copyright © 2014 John Wiley & Sons, Ltd.